Structural organization and regulation of the plasmid-borne type II restriction-modification system Kpn2I from Klebsiella pneumoniae RFL2. - Lubys, A (1999)
Kpn 2I enzymes of a type II restriction-modification (R-M) system from the bacterium Klebsiella pneumoniae strain RFL2 recognize the sequence 5'-TCCGGA-3'. The Kpn 2I R-M genes have been cloned and expressed in Escherichia coli. DNA sequence analysis revealed the presence of two convergently transcribed open reading frames (ORFs) coding for a restriction endonuclease (Enase) of 301 amino acids (34. 8 kDa) and methyltransferase (Mtase) of 375 amino acids (42.1 kDa). The 3'-terminal ends of these genes ( kpn2IR and kpn2IM, respectively) overlap by 11 bp. In addition, a small ORF (gene kpn2IC ) capable of coding for a protein of 96 amino acids in length (10.6 kDa) was found upstream of kpn2IM. The direction of kpn2IC transcription is opposite to that of kpn2IM. The predicted amino acid sequence of this ORF includes a probable helix-turn-helix motif. We show that the product of kpn2IC represses expression of the Kpn 2I Mtase but has no influence on expression of the Enase gene. Such a mode of regulation is unique among R-M systems analyzed so far. The Kpn 2I R-M is located on the K.pneumoniae RFL2 plasmid pKp4.3, which is able to replicate in E.coli cells.